Nitric oxide donor agents for the treatment of ischemia/reperfusion injury in human subjects: a systematic review - Roberts, Brian W; Mitchell, Jessica; Kilgannon, J Hope; Chansky, Michael E; Trzeciak, Stephen (Shock (Augusta, Ga.), 2013)
In animal models, administration of nitric oxide (NO) donor agents has been shown to reduce ischemia/reperfusion (I/R) injury. Our aim was to systematically analyze the biomedical literature to determine the effects of NO-donor agent administration on I/R injury in human subjects. We hypothesized that NO-donor agents reduce I/R injury. We performed a search of Cochrane Library, PubMed, CINAHL, conference proceedings, and other sources with no restriction to language using a comprehensive strategy. Study inclusion criteria were as follows: (a) human subjects, (b) documented periods of ischemia and reperfusion, (c) treatment arm composed of NO-donor agent administration, and (d) use of a control arm. We excluded secondary reports, reviews, correspondence, and editorials. We performed a qualitative analysis to collate and summarize treatment effects according to the recommended methodology from the Cochrane Handbook. Twenty-six studies involving multiple etiologies of I/R injury (10 cardiopulmonary bypass, six organ transplant, seven myocardial infarction, three limb tourniquet) met all inclusion and no exclusion criteria. Six (23%) of 26 were considered high-quality studies as per the Cochrane criteria for assessing risk of bias. In 20 (77%) of 26 studies and four (67%) of six high-quality studies, patients treated with NO-donor agents experienced reduced I/R injury compared with controls. Zero clinical studies to date have tested NO-donor agent administration in patients with cerebral I/R injury (e.g., cardiac arrest, stroke). Despite a paucity of high-quality clinical investigations, the preponderance of evidence to date suggests that administration of NO-donor agents may be an effective treatment for I/R injury in human subjects.